Cultural Issues in Offshore Teams: A Categorization based on Existing Studies - Razavi, Abbas Moshref; Md Nasir, Mohd Hairul Nizam; Yasin, Norizan Mohd; Ahmad, Rodina (Korean Society for Internet Information, 2019)
Cultural and personal issues resulting from dispersed teams are considered to be serious barriers to form trust and organize effective agile teams. However, apart from separate, reported evidence of such issues from work experience, there has been no theoretical classification in literature. This paper provides a list and analysis of common challenges mainly resulting from cultural differences and barriers in Agile Software Development (ASD) offshore teams. The data source comprise Articles published in IEEE, mostly of conferences related to ASD. Among the Articles, papers with concrete evidence of Agile Methods (AM) implementation were selected. The results show that despite the relative significance of such issues, ASD adopters typically still rely on their own experience, and creativity rather than using well-defined methods. Moreover, this study reveals that the notion of trust, as discussed in the literature, mainly refers to maintaining the pace of communication, which is the focal point in ASD. © 2019 KSII.